Geography and decolonisation. (October 2019) - Clayton, Daniel; Kumar, M. Satish
Abstract: This introduction to a special issue on Geography and Decolonisation examines the complex relationship between the discipline of geography and the process of post-war decolonisation. It argues that little attention has been paid to decolonisation within geographical thought and scholarship or to the role that geographers played in the dissolution of colonial empires. It discusses the semantic difficulties surrounding the term decolonisation and examines the ways in which it used in current projects to reshape the academy and the production of knowledge. Serving as an introduction to the five substantive papers in the special issue it identifies cross-cutting themes and sets out a case for further examination of the spatiality of decolonisation. Highlights: Outlines the historiography of post-war decolonisation. Examines how ideas of decolonisation are used within the discipline of geography. Introduces the five papers of a special issue on geography and decolonisation. Argues for further work on the spatiality of decolonisation.